2015
DOI: 10.1002/adma.201502116
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance, Mechanically Flexible, and Vertically Integrated 3D Carbon Nanotube and InGaZnO Complementary Circuits with a Temperature Sensor

Abstract: A vertically integrated inorganic-based flexible complementary metal-oxide-semiconductor (CMOS) inverter with a temperature sensor with a high inverter gain of ≈50 and a low power consumption of <7 nW mm(-1) is demonstrated using a layer-by-layer assembly process. In addition, the negligible influence of the mechanical flexibility on the performance of the CMOS inverter and the temperature dependence of the CMOS inverter characteristics are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 53 publications
6
92
0
Order By: Relevance
“…and dip-coating, 332,343,344 in addition to the widely used thermal evaporation with shadow masking. 172,330,331,340 Different groups have so far demonstrated the potential of integrating p-type pentacene, 172,330,331,340 poly-(9,9-dioctylfluorene-co-bithiophene) (F8T2), 341,342 and semiconducting single walled carbon nanotubes (SWCNTs) 342 The F8T2/IGZO NOT gate shows a gain G ¼ 100 V/V at a maximum supply of 30 V. 342 The same group realized also vertically stacked F8T2/IGZO NAND gates on PET.…”
Section: Materials and Fabrication Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…and dip-coating, 332,343,344 in addition to the widely used thermal evaporation with shadow masking. 172,330,331,340 Different groups have so far demonstrated the potential of integrating p-type pentacene, 172,330,331,340 poly-(9,9-dioctylfluorene-co-bithiophene) (F8T2), 341,342 and semiconducting single walled carbon nanotubes (SWCNTs) 342 The F8T2/IGZO NOT gate shows a gain G ¼ 100 V/V at a maximum supply of 30 V. 342 The same group realized also vertically stacked F8T2/IGZO NAND gates on PET.…”
Section: Materials and Fabrication Techniquesmentioning
confidence: 99%
“…272 Li et al recently demonstrated a flexible 5-stage ring oscillator based on n-type ZnO TFTs and p-type SnO x TFTs, with a maximum oscillation frequency of 18.4 kHz. 177 Recently, solution-processed semiconducting SWCNTs have also been exploited as p-type TFTs 345 and integrated into flexible complementary circuits with n-type sputtered IGZO 103,332,343,344 or spray coated In 2 O 3 TFTs. 145 Bendable hybrid SWCNT/IGZO NOT gates on PI show a maximum gain of 87 V/V, a nearly perfectly centered V M , and a "rail-to-rail" V L (Fig.…”
Section: Materials and Fabrication Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several remarkable studies have been reported to demonstrate the feasibility of three-dimensional TFTs and ICs based on CNT and graphene. [224][225][226][227][228] It is expected that threedimensional all-carbon flexible and transparent electronics will emerge and represent an appealing direction for future research. Additionally, p-type transfer characteristics are usually shown under ambient conditions due to the adsorption of moisture and oxygen.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…It is desirable to convert major carrier types by a doping strategy to obtain n-type transfer characteristics, and further build up CMOS configuration, which is a requirement for realistic all-carbon logic circuits, because CMOS devices have the merits of a higher noise immunity and a lower static power consumption. [226,[228][229][230] All-carbon flexible and transparent TFTs will contribute not only to next-generation display applications but also to novel gas and biological sensors, optical detectors, radio-frequency identification tags and internet-of-things applications. [219,231] These new types of electronics allow integration of sensing, display, and interactive functionalities on a single chip.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%